A study of geopolymerization of mine tailings as construction materials - Jinhong Zhang; Qingming Feng; Dongbo An (International Mineral Processing Congress, 2014)
The application of the geopolymerization of mine tailings as construction materials is hindered by the fact that conventional geopolymerization of mine tailings usually involves a large consumption of alkali, i.e., sodium hydroxide (NaOH), and a long curing time, because of the relatively low reactivity and the high Si/Al ratio of mine tailings when compared to other active resources such as fly ash and clay minerals. The present study is focused on efficiently activating mine tailings, reducing alkali consumption, decreasing curing time and improving compressive strength. We firstly investigate the temperature effect on the alkali activation of mine tailings during geopolymerization. Secondly, the impact of additives, i.e., calcium hydroxide and aluminium oxide, on the compressive strength of samples is studied. Thirdly, different forming pressures have been applied to remove excessive alkali and its impact on samples' strength has been investigated. The results show that a 40 MPa unconfined compressive strength (UCS) can be achieved with the geopolymerization samples after mine tailings are activated by sodium hydroxide at 170°C for 1 hour with the addition of calcium hydroxide and alkali dissolved aluminium oxide, further compressed with a 10 MPa forming pressure and finally cured at 90°C for 3 days. The findings of the present work provide a novel method for the geopolymerization of mine tailings as construction materials.